2018
DOI: 10.1109/tasc.2018.2804906
|View full text |Cite
|
Sign up to set email alerts
|

3-D Modeling of Coils for Pulsed Field Magnetization of HTS Bulk Pellets in an Electrical Machine

Abstract: Abstract-In this work, we propose to study and design a coil used to magnetize, by means of a Pulsed Field Magnetization (PFM) process, an inductor of a radial flux superconducting machine with one pair of poles. Each pole contains four similar HTS bulks of 30 mm diameter arranged in a square pattern. The cryostat already exists for this application and the temperature of the HTS bulks can vary from 4.2 K to their critical temperature, in transient state. For a given primary source of energy, here a capacitor … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 19 publications
0
6
0
2
Order By: Relevance
“…The interest in studying the magnetic properties of hightemperature superconductors (HTSs) is growing every year. Numerous studies have shown that bulk superconductors and stacks of HTS tapes are capable of trapping magnetic fields of several teslas or higher and can therefore be used as pseudopermanent trapped field magnets (TFMs) [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18]. The range of potential practical applications of such magnets extends from magnetic bearings and levitation devices to motors and highfield magnets [1,2,16,[19][20][21][22][23].…”
Section: Introductionmentioning
confidence: 99%
“…The interest in studying the magnetic properties of hightemperature superconductors (HTSs) is growing every year. Numerous studies have shown that bulk superconductors and stacks of HTS tapes are capable of trapping magnetic fields of several teslas or higher and can therefore be used as pseudopermanent trapped field magnets (TFMs) [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18]. The range of potential practical applications of such magnets extends from magnetic bearings and levitation devices to motors and highfield magnets [1,2,16,[19][20][21][22][23].…”
Section: Introductionmentioning
confidence: 99%
“…H(Ω) is the finite dimensional subset of the curl-conform space H(curl; Ω) generated by Whitney edge elements on the mesh in Ω [5]. (H 3 (Ωm)) 3 is the space of piecewise constant vector functions (3 components) per element in Ωm. * For the ā-formulation, choosing σ = 0 in Ω C c makes the system singular, but this is not necessarily an issue as some linear solvers do not require uniqueness of the solution.…”
Section: Volume-coupled Formulationmentioning
confidence: 99%
“…Additionally, a fuel cell could be used to power the coils as described in [26]. All the superconducting pellets used in the TF-FPDI must be equipped with a coil system wrapped around them [27] to allow for PFM (violet rings in Figs. 3 to 5).…”
Section: Design Of Fdpi With Tf Magnetsmentioning
confidence: 99%